Guidelines for the nomenclature of genetic elements in tunicate genomes. Issue 1 (3rd October 2014) - Stolfi, Alberto; Sasakura, Yasunori; Chalopin, Domitille; Satou, Yutaka; Christiaen, Lionel; Dantec, Christelle; Endo, Toshinori; Naville, Magali; Nishida, Hiroki; Swalla, Billie J.; Volff, Jean‐Nicolas; Voskoboynik, Ayelet; et al.
Summary Tunicates are invertebrate members of the chordate phylum, and are considered to be the sister group of vertebrates. Tunicates are composed of ascidians, thaliaceans, and appendicularians. With the advent of inexpensive high‐throughput sequencing, the number of sequenced tunicate genomes is expected to rise sharply within the coming years. To facilitate comparative genomics within the tunicates, and between tunicates and vertebrates, standardized rules for the nomenclature of tunicate genetic elements need to be established. Here we propose a set of nomenclature rules, consensual within the community, for predicted genes, pseudogenes, transcripts, operons, transcriptional cis‐regulatory regions, transposable elements, and transgenic constructs. In addition, the document proposes guidelines for naming transgenic and mutant lines. genesis 53:65–78, 2015. © 2014 Wiley Periodicals, Inc.